2013
DOI: 10.1080/08870446.2013.866673
|View full text |Cite
|
Sign up to set email alerts
|

Being a non-drinking student: An interpretative phenomenological analysis

Abstract: Recent research suggests that safer student alcohol consumption might be assisted by understanding how social occasions are managed by non-drinkers. In-depth, semi-structured interviews with five 19-22 year old non-drinking English undergraduates were subjected to interpretative phenomenological analysis (IPA). We present five inter-linked themes: 'living with challenges to non-drinking'; 'seeing what goes on in drinking environments'; 'dealing with conversations about non-drinking ('making excuses vs. coming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 32 publications
3
82
0
Order By: Relevance
“…One of the main concerns raised by HSM users was that it is difficult to be a non‐drinker in a society where drinking is not just normative, but expected. Some participants reported feeling socially stigmatised, as has been found in other research . In previous research, FebFast participants reported the impression that they had violated social norms through inadequate participation in collective drinking occasions and ritualised celebrations, and disrupting group dynamics and social expectations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the main concerns raised by HSM users was that it is difficult to be a non‐drinker in a society where drinking is not just normative, but expected. Some participants reported feeling socially stigmatised, as has been found in other research . In previous research, FebFast participants reported the impression that they had violated social norms through inadequate participation in collective drinking occasions and ritualised celebrations, and disrupting group dynamics and social expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that whilst battling the temptation of drinking, non‐drinkers also have to concern themselves with how their decision not to drink affects others . In an Australian study, non‐drinking participants attempted to either conceal or present their non‐drinking in such a way as to avoid challenging social norms around drinking (such as pretending to be drinking alcohol or making up a “culturally legitimate” health excuse), but many stopped socialising with the same group of people over time and instead focused on activities that did not involve alcohol…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from neither the LGC nor intention to treat analyses offered support for hypothesis 2: Completing both mental simulation exercises did not lead to steeper rates of change in drinking behaviour than completing either outcome or process simulations on their own and were, in fact, no better than the drinks diary control condition. However, imagining how non-drinking might be most successfully achieved within social situations seems likely to be integral to developing the necessary drink refusal self-efficacy skills required to be socially present as a non-drinker, a behaviour that has been suggested to carry unique and significant social challenges (Conroy & de Visser, 2014). However, contrary to hypotheses 3(a) and 3(b), ratings of prototypical non-drinkers as comparatively more sociable did not mediate intervention effects related to the reduction of weekly unit intake or HED for any condition.…”
Section: Discussionmentioning
confidence: 99%